2015
DOI: 10.1002/bit.25880
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nitric oxide (NO) redox reactions contribution to nitrous oxide (N2O) formation during nitrification using a multispecies metabolic network model

Abstract: Over the coming decades nitrous oxide (N2O) is expected to become a dominant greenhouse gas and atmospheric ozone depleting substance. In wastewater treatment systems, N2O is majorly produced by nitrifying microbes through biochemical reduction of nitrite (NO2(-)) and nitric oxide (NO). However it is unknown if the amount of N2O formed is affected by alternative NO redox reactions catalyzed by oxidative nitrite oxidoreductase (NirK), cytochromes (i.e., P460 [CytP460] and 554 [Cyt554 ]) and flavohemoglobins (Hm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…NO x gas measurements were made from such suspensions of concentrated QS-proficient or -deficient N. winogradskyi cells during 24 h of NO 2 − oxidation. We predicted that an increase in expression of the nirK cluster genes under QS-proficient conditions would either increase NO x production as earlier studies have suggested (3234) or decrease NO x production by consuming NO as previously reported (3436). …”
Section: Resultsmentioning
confidence: 80%
“…NO x gas measurements were made from such suspensions of concentrated QS-proficient or -deficient N. winogradskyi cells during 24 h of NO 2 − oxidation. We predicted that an increase in expression of the nirK cluster genes under QS-proficient conditions would either increase NO x production as earlier studies have suggested (3234) or decrease NO x production by consuming NO as previously reported (3436). …”
Section: Resultsmentioning
confidence: 80%
“…To date, most genome-scale and metabolic models of nitrification have focused on biotic reactions (17, 22, 23, 36). While this approach simplifies the construction of models, it neglects the importance of abiotic chemistry in the N cycle (13).…”
Section: Discussionmentioning
confidence: 99%
“…Among AOB, the genus Nitrosospira is usually most numerous in soils, and genomic data are available for assembly into genome-scale metabolic models (5254). Perez-Garcia et al (17) constructed a stoichiometric metabolic model of several AOB and NOB based on genomic data and published studies of nitrifying mixed cultures in wastewater treatment, but specific kinetic information and genome-scale models of many species are still lacking. Before genome-scale metabolic models of these microorganisms can be fully completed, growth and energy yield parameters and nutrient and O 2 affinity data are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations